Treatment method of hydrofluoric acid-sulfuric acid process tantalum-niobium tailings
By mixing the tantalum niobium tailslag with dilute sulfuric acid solution, performing reduction reaction and crystallization treatment, ferrous sulfate and fluorine-containing compounds are extracted, and further purified through defluorination reaction, the problem of difficult recovery of iron and fluorine resources in tantalum niobium tailslag is solved, achieving efficient resource utilization and environmental safety.
Patent Information
- Application Number
- CN202510037287.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to efficiently recover iron and fluorine resources in tantalum niobium tailings, resulting in waste of resources and increased environmental risks.
The tantalum niobium tailings obtained by smelting the hydrofluoric acid-sulfuric acid method were mixed with a dilute sulfuric acid solution, and the reduction reaction and crystallization treatment were carried out to extract ferrous sulfate and fluorine-containing compounds, and further purified by defluorination reaction.
It has achieved efficient recycling and utilization of iron and fluorine resources in tantalum niobium tailings, improved the utilization value of resources, and reduced environmental risks and resource waste.
Smart Images

Figure CN119822419A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of tantalum-niobium ore tailings recovery, and in particular to a method for treating tantalum-niobium tailings produced by a hydrofluoric acid-sulfuric acid process. Background Art
[0002] Tantalum and niobium are both rare metals and important strategic reserve resources. They have good physical and chemical properties and are widely used in electronics, steel, aerospace, chemical industry, nuclear industry and other fields. Tantalum and niobium industrial minerals mainly include tantalate and titanium tantalate niobate; tantalate mainly includes tantalite and niobium manganese ore, and titanium tantalate niobate mainly includes pyrochlore and fine quartz.
[0003] At present, the smelting methods of tantalum and niobium include hydrofluoric acid method, high-temperature sulfuric acid method, hydrofluoric acid-sulfuric acid method, alkali fusion method and alkali solution method. Among them, the hydrofluoric acid-sulfuric acid method is the most widely used. Its main process is to extract the tantalum and niobium ore by decomposing it with hydrofluoric acid and sulfuric acid, and then extracting the tantalum and niobium. A large amount of tantalum and niobium tailings are produced at the same time. The tantalum and niobium tailings of the hydrofluoric acid-sulfuric acid method contain residual acid (hydrofluoric acid, sulfuric acid) and inorganic components (Fe 3+ , Fe 2+ , Mn 2+ 、Al 3+ ) etc. At present, the general method for treating tantalum-niobium tailings is to seal them up. However, with the development of the tantalum-niobium industry, the storage volume of tantalum-niobium tailings is increasing. The tin, tantalum-niobium, rare earth and other resources contained in them are important secondary resources. Recycling them can reduce storage environmental risks and reduce resource waste. However, the resource utilization rate of resources such as tin and rare earth is severely restricted by the iron and fluorine in the tailings. Therefore, it is necessary to provide a process for efficiently recycling fluorine and iron from tantalum-niobium slag. Summary of the invention
[0004] Based on this, one or more embodiments of the present application provide a processing method capable of recovering ferrous sulfate and fluorine-containing compounds from tantalum-niobium tailings obtained by hydrofluoric acid-sulfuric acid smelting.
[0005] According to a first aspect of an embodiment of the present application, a method for treating tantalum-niobium tailings produced by a hydrofluoric acid-sulfuric acid process is provided, comprising the following steps:
[0006] The tantalum-niobium tailings obtained by the hydrofluoric acid-sulfuric acid process are mixed with a dilute sulfuric acid solution, stirred and reacted at 40°C to 80°C for 30min to 300min, and filtered to obtain a leachate and a washing residue;
[0007] The leaching solution is mixed with iron powder to undergo a reduction reaction, and filtered to obtain a purified solution;
[0008] The purified liquid is subjected to cooling and crystallization treatment, and filtered to obtain crude ferrous sulfate and crystallization mother liquor;
[0009] The pH value of the crystallization mother liquor is adjusted to 2.0-6.0 by using a pH adjusting agent, mixed with a defluorinating agent for defluorination reaction, and filtered to obtain a fluorine-containing compound and a recycled mother liquor.
[0010] In some embodiments, the processing method further comprises the following steps:
[0011] Dissolving the crude ferrous sulfate at 60° C. to 70° C., and obtaining ferrous sulfate and a recrystallization mother liquor by recrystallization and filtration;
[0012] The pH value of the recrystallization mother liquor is adjusted to 2.0-6.0 by using a pH adjusting agent, mixed with a defluorinating agent for defluorination reaction, and filtered to obtain a fluorine-containing compound and a recycled mother liquor.
[0013] In some embodiments, before the leaching solution is mixed with the iron powder for reduction reaction, the following steps are also included:
[0014] The leaching solution is mixed with tantalum-niobium tailings, stirred and reacted at 40° C. to 80° C. for 30 min to 300 min, and filtered while keeping warm.
[0015] In some embodiments, the concentration of the dilute sulfuric acid solution is 10 g / L to 50 g / L.
[0016] In some embodiments, the ratio of the volume of the dilute sulfuric acid solution to the mass of the tantalum-niobium tailings is (0.5 mL to 2 mL): 1 g;
[0017] Optionally, the mass ratio of the volume of the dilute sulfuric acid solution to the tantalum-niobium tailings is (2 mL~3 mL): 1 g.
[0018] In some of the embodiments, the tantalum-niobium tailings obtained by the hydrofluoric acid-sulfuric acid process are mixed with the recycled mother liquor and the dilute sulfuric acid solution.
[0019] In some embodiments, the processing method satisfies at least one of the following characteristics:
[0020] (1) In the step of obtaining the leaching solution and the washing residue by heat preservation filtration, the temperature of the heat preservation filtration is 55°C to 65°C;
[0021] (2) The final temperature of the cooling crystallization is 10°C to 25°C;
[0022] (3) The temperature of the defluorination reaction is 50°C to 70°C, and the time is 1h to 5h.
[0023] In some of the embodiments, the ratio of the molar number of the iron powder to the molar number of the iron powder theoretically required for the reduction reaction is (1.2~2):1.
[0024] In some embodiments, the processing method satisfies at least one of the following characteristics:
[0025] (1) The defluorination agent includes one or more of magnesium sulfate, aluminum sulfate, sodium sulfate and rare earth sulfate;
[0026] (2) The pH adjuster includes one or more of ammonia water, ammonium bicarbonate, sodium hydroxide and sodium carbonate.
[0027] In some embodiments, the ratio of the number of moles of the defluorinating agent to the number of moles of the defluorinating agent theoretically required for the defluorinating reaction is (0.85-1):1.
[0028] Compared with the traditional technology, this application has the following beneficial effects:
[0029] The present invention relates to a method for treating the tantalum-niobium tailings obtained by the hydrofluoric acid-sulfuric acid process. The tantalum-niobium tailings obtained by the hydrofluoric acid-sulfuric acid process are mixed with a dilute sulfuric acid solution and fully reacted and leached under specific temperature conditions to obtain a tantalum-niobium tailings containing Fe 3+ , Fe 2+ 、F - Plasma leaching solution; by reducing the leaching solution, Fe 3+ Reduction to Fe 2+ , and then ferrous sulfate crystals are precipitated by crystallization, and purified ferrous sulfate is obtained by dissolving and recrystallizing under specific temperature conditions; the crystallization mother liquor and the recrystallization mother liquor are further defluorinated to obtain fluorine-containing compounds and recycled mother liquor; the above-mentioned tantalum-niobium tailings treatment method extracts ferrous sulfate with high purity from the tantalum-niobium tailings, and the mother liquor can be regenerated and reused after defluorination; the obtained fluorine-containing compounds can be used as raw materials in the fluorine chemical industry, thereby improving the resource utilization value of fluorine. The above-mentioned method can realize the effective utilization of resources such as iron and fluorine in the tantalum-niobium tailings, and at the same time realize the reduction and harmlessness of the tantalum-niobium tailings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 It is a schematic flow chart of the tantalum-niobium tailings treatment method in the implementation method of the present application. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0034] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0035] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0036] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present invention, it is within the scope disclosed in the embodiment description of the present invention. Specifically, the weight described in the embodiment description of the present invention can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0037] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0038] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0039] In traditional technology, the treatment method for tantalum niobium tailings obtained by hydrofluoric acid-sulfuric acid smelting is mainly the calcium solidification method, that is, using calcium to solidify fluorine, iron, manganese and other elements together, and then treating the formed hazardous waste slag; although this method removes elements such as fluorine, iron, manganese in the tailings, it is impossible to achieve secondary utilization of the hazardous waste slag, and the resource recycling efficiency is low.
[0040] Based on this, the present application creatively proposes a new method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid method, which can achieve efficient recovery and utilization of resources in the tailings.
[0041] See also Figure 1 In one embodiment of the present application, a method for treating tantalum-niobium tailings produced by a hydrofluoric acid-sulfuric acid process is provided, including S10, S30, S40 and S60.
[0042] S10: mixing the tantalum-niobium tailings obtained by smelting with a hydrofluoric acid-sulfuric acid method with a dilute sulfuric acid solution, stirring and reacting at 40° C. to 80° C. for 30 min to 300 min, and filtering at a temperature of 40° C. to obtain a leachate and a washing residue;
[0043] S30: mixing the leaching solution and the iron powder to perform a reduction reaction, and filtering to obtain a purified solution;
[0044] S40: cooling and crystallizing the purified liquid, filtering to obtain crude ferrous sulfate and a crystallization mother liquor;
[0045] S60: The pH value of the crystallization mother liquor is adjusted to 2.0-6.0 by using a pH adjusting agent, mixed with a defluorinating agent for defluorination reaction, and filtered to obtain a fluorine-containing compound and a recycled mother liquor.
[0046] In the above treatment method of the present application, the tantalum-niobium tailings obtained by smelting with hydrofluoric acid-sulfuric acid method are mixed with dilute sulfuric acid solution and fully reacted and leached under specific temperature conditions to obtain a tantalum-niobium tailings containing Fe 3+ , Fe 2+ , Mn 2+ 、F - Plasma leaching solution; by reducing the leaching solution, Fe 3+ Reduction to Fe 2+, and then precipitate ferrous sulfate crystals by crystallization, and dissolve and recrystallize under specific temperature conditions to obtain purified ferrous sulfate; under this temperature condition, the solubility of FeF2 is relatively large, and the effect of temperature on its solubility is relatively small, it can be stably present in the solution and is difficult to precipitate by cooling, so the present application further adds a defluorinating agent to the F in the crystallization mother liquor and the recrystallization mother liquor - Defluorination treatment is carried out to obtain fluorine-containing compounds with higher purity. The above-mentioned treatment method extracts ferrous sulfate and fluorine-containing compounds with higher purity from the tantalum-niobium tailings obtained by the hydrofluoric acid-sulfuric acid method, thereby realizing the efficient recycling and utilization of tantalum-niobium tailings resources.
[0047] The present application first precipitates the sulfate ions in the leachate, thereby reducing the difficulty in dissolving the fluoriding agent due to the common ion effect, increasing the solubility of the defluoriding agent in the recrystallization mother liquor and the crystallization mother liquor, and thus improving the defluorination rate of the mother liquor. If the sulfate ion concentration in the mother liquor is too high, the solubility of the fluoriding agent is low after adding it, and it cannot react with the fluoride ions in the mother liquor to form a precipitate, but slowly forms a colloidal or flocculent substance.
[0048] It should be noted that the hydrofluoric acid-sulfuric acid method tantalum-niobium tailings are smelting tailings formed by decomposing tantalum-niobium ore using hydrofluoric acid and sulfuric acid, and then extracting the ore pulp. The hydrofluoric acid-sulfuric acid method tantalum-niobium tailings mainly contain residual acid (hydrofluoric acid, sulfuric acid), organic components (MIBK, 2-octanol, etc.) and inorganic components (such as sulfates or fluoride salts of iron, manganese, and aluminum).
[0049] As an example, the reaction temperature after the tantalum-niobium tailings and the dilute sulfuric acid solution are mixed in S10 can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, or any value within the range formed by any two of the above point values. Controlling the reaction temperature within the above range can increase the leaching rate of effective ions in the tailings.
[0050] Furthermore, the reaction temperature of the tantalum-niobium tailings after mixing with the dilute sulfuric acid solution in S10 is 50°C to 70°C.
[0051] As an example, the reaction time after the tantalum-niobium tailings are mixed with the dilute sulfuric acid solution in S10 can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, 210 min, 220 min, 230 min, 240 min, 250 min, 260 min, 270 min, 280 min, 290 min, 300 min, or any value within the range formed by any two of the above point values.
[0052] Furthermore, the reaction time after the tantalum-niobium tailings in S10 are mixed with the dilute sulfuric acid solution is 60 min to 180 min.
[0053] In some of the embodiments, the washing residue in S10 contains the following elements: O, F, S, Fe, Mn, Sn, Al, Zr, Si, Ca, TRE, U, etc.
[0054] In some of the embodiments, the concentration of the dilute sulfuric acid solution in S10 is 10 g / L to 50 g / L.
[0055] As an example, the concentration of the dilute sulfuric acid solution can be 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, or any value within the range formed by any two of the above point values. Controlling the concentration of the dilute sulfuric acid solution within the above specific range can not only promote the subsequent reduction reaction of the iron powder to proceed quickly, but also will not increase the amount of iron powder required for the reduction reaction.
[0056] Furthermore, the concentration of the dilute sulfuric acid solution in S10 is 20 g / L to 50 g / L.
[0057] In some examples, the pH value of the dilute sulfuric acid solution in S10 is 0.5-2.0.
[0058] In some of the embodiments, the ratio of the volume of the dilute sulfuric acid solution in S10 to the mass of the tantalum-niobium tailings is (0.5 mL~2 mL): 1 g.
[0059] As an example, the ratio of the volume of the dilute sulfuric acid solution to the mass of the tantalum-niobium tailings can be 0.5 mL: 1 g, 0.6 mL: 1 g, 0.7 mL: 1 g, 0.8 mL: 1 g, 0.9 mL: 1 g, 1 mL: 1 g, 1.1 mL: 1 g, 1.2 mL: 1 g, 1.3 mL: 1 g, 1.4 mL: 1 g, 1.5 mL: 1 g, 1.6 mL: 1 g, 1.7 mL: 1 g, 1.8 mL: 1 g, 1.9 mL: 1 g, 2 mL: 1 g, or any value within the range formed by any two of the above point values. Controlling the ratio of the volume of the dilute sulfuric acid solution to the mass of the tantalum-niobium tailings within the above range makes the slurry viscosity moderate and easy to stir, and can reduce the difficulty of concentrated crystallization, thereby obtaining high-concentration ferrous sulfate heptahydrate.
[0060] In some examples, the volume ratio of the dilute sulfuric acid solution to the mass ratio of the tantalum-niobium tailings is (1 mL~2 mL): 1 g.
[0061] In some of the embodiments, the stirring speed of the stirring reaction is 400 r / min~800 r / min.
[0062] As an example, the stirring speed can be 400r / min, 450r / min, 500r / min, 550r / min, 600r / min, 650r / min, 700r / min, 750r / min, 800r / min, or any value within the range formed by any two of the above point values.
[0063] It should be noted that the stirring speed of the stirring reaction is not limited to the above, and may be other.
[0064] In some of the embodiments, in the step of heat-insulating filtration to obtain the leachate and the washing residue in S10, the temperature of the heat-insulating filtration is 55°C to 65°C.
[0065] As an example, the temperature of the heat preservation filtration can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, or any value within the range formed by any two of the above point values. When the temperature is controlled within the above range during filtration, the solubility of FeSO4·7H2O is relatively large, which is conducive to the dissolution of ferrous sulfate into the leachate, and will not precipitate into the slag phase.
[0066] In some embodiments, S10 includes: mixing the tantalum-niobium tailings obtained by hydrofluoric acid-sulfuric acid smelting with the recycled mother liquor and the dilute sulfuric acid solution. That is, the recycled mother liquor obtained by filtering S60 is circulated for leaching the tantalum-niobium tailings.
[0067] In some of the embodiments, after S10 and before S30, S20 is further included.
[0068] S20: Mix the leaching solution with the tantalum-niobium tailings, stir and react at 40°C-80°C for 30min-300min, and filter while keeping warm.
[0069] The reaction temperature and reaction time in S20 may be the same as or different from those in S10.
[0070] It can be understood that in S20, the second leachate and the second washing residue are obtained by heat preservation and filtration. The second leachate obtained by filtration is then used in S30 to mix with iron powder for reduction reaction.
[0071] In some examples, after S10 and before S30, S20 is performed at least once, for example, once, twice, three times or more times, that is, the leaching solution and the tantalum-niobium tailings are repeatedly mixed and leached, and the leaching solution is circulated and re-leached.
[0072] The concentration of ferrous sulfate in the leachate is saturated by repeatedly mixing and leaching the leachate with the tantalum-niobium tailings; thus, during the crystallization process, saturation can be achieved without concentration, so cooling crystallization can be performed directly.
[0073] In some of the embodiments, the ratio of the molar number of iron powder in S30 to the molar number of iron powder theoretically required for the reduction reaction is (1.2-2):1.
[0074] By adding iron powder, Fe 3+ Reduction to Fe 2+ On the one hand, it can increase the concentration of ferrous iron, which is beneficial to the crystallization of ferrous sulfate; on the other hand, it can avoid the co-precipitation of iron when adjusting the pH value to precipitate fluorine, thereby improving the separation effect of iron and fluorine.
[0075] It can be understood that the present application does not specifically limit the shape, size, etc. of the iron powder. For example, it can also be iron filings, etc.
[0076] In some examples, the filtrate obtained by filtering the mixture of the leaching solution and the iron powder contains reduced iron slag.
[0077] As an example, the ratio of the molar number of iron powder to the molar number of iron powder theoretically required for the reduction reaction can be 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, or any value within the range formed by any two of the above ratios.
[0078] It should be noted that the leaching solution contains Fe in the form of Fe2(SO4)3 3+ After adding iron powder, the following reaction occurs: Fe2(SO4)3+Fe=3FeSO4. 3+When the molar ratio of Fe to Fe2(SO4)3 is (0.55~1.2):1, the molar ratio of Fe to Fe2(SO4)3 is about (1.2~2):1, that is, the amount of iron powder added is 1.2~2 times the theoretical amount required. When the amount of iron powder added is controlled within the above range, the Fe in the solution can be 3+ The complete reduction to form ferrous sulfate crystals with higher purity can further adjust the pH value of the solution without causing excess and waste of raw materials.
[0079] Ferrous sulfate is widely used in agriculture, water treatment, industry, environmental protection, medicine, food, laboratory research and other fields; especially with the rapid growth of lithium iron phosphate cathode materials in the new energy field, the market demand for ferrous sulfate as a raw material for lithium iron phosphate has also increased. Recycling the large amount of iron ions in the tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid method can not only reduce the threat of tantalum-niobium tailings to the environment, but also realize the transformation of waste into treasure.
[0080] In some embodiments, the step of cooling crystallization treatment in S40 includes: heating and concentrating the purified liquid, and cooling it to precipitate crystals.
[0081] In some examples, the heating and concentration process also includes a stirring step, and the wall sticking phenomenon can be reduced by stirring.
[0082] It can be understood that if the leaching solution and the tantalum-niobium tailings are repeatedly mixed and leached in S20 to make the concentration of ferrous sulfate in the leaching solution reach saturation, then there is no need to heat and concentrate during the cooling crystallization treatment in S40, and direct cooling is sufficient.
[0083] In some examples, the final temperature of cooling in S40 is 10° C. to 25° C. As an example, the final temperature of cooling can be 10° C., 11° C., 12° C., 13° C., 14° C., 15° C., 16° C., 17° C., 18° C., 19° C., 20° C., 21° C., 22° C., 23° C., 24° C., 25° C., or any value within the range formed by any two of the above point values.
[0084] In some embodiments, the recrystallization step in S50 includes: heating and concentrating the purified liquid, and cooling it to precipitate crystals.
[0085] The solution can be saturated in advance through concentration and crystallization; in order to simplify the workload of concentration and crystallization treatment, the liquid-to-solid ratio of tantalum-niobium tailings to dilute sulfuric acid solution in S10 should not be too high.
[0086] In some examples, the final cooling temperature in S50 is 10° C. to 25° C. As an example, the final cooling temperature may be 10° C., 11° C., 12° C., 13° C., 14° C., 15° C., 16° C., 17° C., 18° C., 19° C., 20° C., 21° C., 22° C., 23° C., 24° C., 25° C., or any value within the range formed by any two of the above point values.
[0087] It should be noted that the final temperature of cooling in S40 and the final temperature of cooling in S50 may be the same or different.
[0088] In some of the embodiments, after S40 and before S60, S50 is further included.
[0089] S50: dissolving crude ferrous sulfate at 60°C-70°C, and obtaining ferrous sulfate and recrystallization mother liquor through recrystallization and filtration.
[0090] At this time, S60 includes: using a pH regulator to adjust the pH value of the crystallization mother liquor and the recrystallization mother liquor to 2.0-6.0, mixing with a defluorinating agent to perform a defluorination reaction, filtering to obtain a fluorine-containing compound and a recycled mother liquor.
[0091] As an example, the temperature for dissolving crude ferrous sulfate in S50 can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, or any value within the range formed by any two of the above point values. Before recrystallization, the crude ferrous sulfate is dissolved at the above specific temperature, which can fully dissolve the ferrous sulfate to form a saturated solution without dissolving too many other impurities. Furthermore, the solution obtained after dissolution is heated and concentrated, and cooled to precipitate crystals, so that ferrous sulfate crystals with higher purity can be obtained.
[0092] In addition, when the temperature of the crude ferrous sulfate being dissolved is within the above range, ferrous sulfate can be dissolved to form a saturated solution, while FeF2 has a large solubility and the temperature has a relatively small effect on its solubility, so it can be stably present in the solution and is difficult to separate out by cooling; therefore, FeF - The ions still remain in the crystallization mother liquor and the recrystallization mother liquor.
[0093] Ferrous sulfate heptahydrate reaches its maximum solubility (107.6 g / 100 g water) at about 60 ° C, and its solubility decreases when the temperature is lowered to room temperature (48 g / 100 g water), and its solubility is about 57.8 g / 100 g water when the temperature is raised to 100 ° C. Under low temperature conditions, the solubility of ferrous sulfate heptahydrate can be increased by increasing the liquid-solid ratio, but the workload of concentrated crystallization recovery will increase. Therefore, the above temperature is used in this application to dissolve crude ferrous sulfate.
[0094] As an example, after adding the pH adjuster, the pH value of the crystallization mother liquor and the recrystallization mother liquor can be 2.0, 3.0, 4.0, 5.0, 6.0, or any value within the range formed by any two of the above point values.
[0095] By adjusting the pH value of the crystallization mother liquor and the recrystallization mother liquor to 2.0-6.0, the F - It can react with the defluorinating agent to form a precipitate to obtain a fluorine-containing compound; it should be noted that the pH value of the crystallization mother liquor and the recrystallization mother liquor should not be too high. If the pH value is too high, Fe 2+ Oxidation, while Fe 2+ It will hydrolyze and the resulting fluorine compound will be of low purity.
[0096] At the same time, the recycled mother liquor obtained after the crystallization mother liquor and the recrystallization mother liquor are purified can be recycled and used in a new round of tantalum-niobium tailings treatment method after adding an appropriate amount of dilute sulfuric acid to adjust the acidity to 0.5-2.0. Specifically, in S10, the recycled mother liquor after the acidity adjustment is mixed with the tantalum-niobium tailings to make the Fe in the tantalum-niobium tailings 3+ , Fe 2+ , Mn 2+ 、F - Wait for leaching.
[0097] Returning the recycled mother liquor to the leaching of tantalum-niobium tailings in S10 can achieve dynamic balance, reduce water consumption, increase the degree of ion enrichment, and save energy.
[0098] In some embodiments, the pH adjuster includes one or more of ammonia, ammonium bicarbonate, sodium hydroxide and sodium carbonate.
[0099] In some embodiments, the defluorinating agent includes one or more of magnesium sulfate, aluminum sulfate, sodium sulfate, and rare earth sulfate.
[0100] The leaching solution obtained by mixing tantalum-niobium tailings with a dilute sulfuric acid solution contains a large amount of fluorine, sulfate, etc. If the above-mentioned defluorinating agent is directly used for defluorination, the solubility of the defluorinating agent may be very small due to the common ion effect, making it difficult to achieve the purpose of defluorination; therefore, the present application achieves the purpose of efficient defluorination by first removing a large amount of sulfate in the solution and then performing defluorination.
[0101] The above defluorinating agent can react with F in the crystallization mother liquor and the recrystallization mother liquor under specific pH conditions. - The reaction forms precipitates such as AlF3, MnF2, FeF3, Na3AlF6 or REF3, thereby obtaining fluorine-containing compounds. At the same time, the use of the above-mentioned specific types of defluorinating agents can reduce the introduction of new impurities into the crystallization mother liquor and the recrystallization mother liquor, so that the crystallization mother liquor and the recrystallization mother liquor can be reused for leaching the tantalum-niobium tailings after simple adjustment.
[0102] In some of the embodiments, the temperature of the defluorination reaction in S60 is 50° C. to 70° C., and the time is 1 h to 5 h.
[0103] As an example, the temperature of the defluorination reaction can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, or any value within the range formed by any two of the above point values.
[0104] As an example, the defluorination reaction time can be 1 h, 2 h, 3 h, 4 h, 5 h, or any value within the range formed by any two of the above point values.
[0105] In some of the embodiments, the ratio of the number of moles of the defluorinating agent in S60 to the number of moles of the defluorinating agent theoretically required for the defluorinating reaction is (0.85-1):1.
[0106] As an example, the ratio of the number of moles of the defluorinating agent to the number of moles of the defluorinating agent theoretically required for the defluorinating reaction can be 0.85:1, 0.86:1, 0.87:1, 0.88:1, 0.89:1, 0.9:1, 0.91:1, 0.92:1, 0.93:1, 0.94:1, 0.95:1, 0.96:1, 0.97:1, 0.98:1, 0.99:1, 1:1, or any value within the range formed by any two of the above point values.
[0107] It can be understood that when the pH value of the crystallization mother liquor and the recrystallization mother liquor is adjusted before adding the defluorinating agent, the Al 3+ and Fe 3+ (Part of Fe 2+ is oxidized) and F in solution - Combine to form a precipitate; and in order not to introduce additional impurities, the amount of defluorinating agent added is preferably slightly less than the theoretical amount.
[0108] By adding a defluorinating agent, F - The fluorine-containing compounds can be precipitated from the mother liquor, thus achieving the purpose of purifying the mother liquor and reducing the harm of the fluorine-containing mother liquor to the environment. In addition, the fluorine-containing compounds recovered above can be used to prepare cryolite for electrolytic aluminum, blast furnace slag-making agent, cement and ceramics.
[0109] Compared with the traditional calcium fluoride precipitation defluorination, the fluorine-containing compounds formed in the present application can be reused as chemical products, thereby improving the resource utilization value of fluorine.
[0110] The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid method of the present application first precipitates ferrous sulfate in the solution by crystallization, and then adds a defluorinating agent to precipitate fluorine; in this way, the saturation of sulfate ions in the solution is reduced after the precipitation of ferrous sulfate, and the defluorinating agent will not be unable to dissolve due to the common ion effect when it is added.
[0111] The above-mentioned treatment method of the present application can recover high-purity ferrous sulfate and fluorine-containing compounds from the discarded hydrofluoric acid-sulfuric acid method tantalum niobium tailings, thereby realizing the recycling of resources; and can separate the residual acid, fluorine, iron and other inorganic components in the tantalum niobium tailings that may pose a threat to the environment, thereby reducing the harm of fluorine-containing wastewater to the environment, and solving the problem of difficult treatment of tantalum niobium tailings faced by enterprises.
[0112] The above-mentioned treatment method of the present application has at least the advantages of simple process, high recycling rate and low cost.
[0113] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0114] Example 1
[0115] (1) XRF composition analysis was performed on the dried tantalum-niobium tailings sample. The results are shown in the following table.
[0116] Table 1
[0117]
[0118] (2) Weigh 500 g of the dried tantalum-niobium tailings sample into a beaker, add 1000 mL of a 50 g / L H2SO4 solution preheated to 60°C; maintain 60°C, stir at 600 r / min for 2 h, and filter to obtain 1150 mL of leaching solution and 190 g of washing residue.
[0119] (3) The concentration of total iron (TFe) in the leaching solution is 61 g / L, Fe 3+ The concentration is 16.5g / L, 12g of iron filings are added to the solution, stirred and reacted at 60℃ for 1h, and filtered while hot to obtain 1100mL of purified liquid and 5g of reduced iron slag.
[0120] (4) The purified liquid was boiled under stirring, concentrated until a small amount of crystals precipitated, cooled to 25°C and filtered to obtain 293 g of crude ferrous sulfate heptahydrate and 400 mL of crystallization mother liquor.
[0121] (5) Dissolve the crude ferrous sulfate heptahydrate in 60°C water, cool to 25°C with stirring, and recrystallize three times to obtain 150 g of ferrous sulfate with a purity of 98.5%.
[0122] (6) The mother liquor from the first recrystallization was mixed with the mother liquor from the crystallization to obtain 500 mL of mixed liquid, and the pH value was adjusted to 5.0 with sodium hydroxide. The fluoride ion concentration in the mixed liquid was detected to be 40 g / L; 110 g of defluorinating agent MgSO4·7H2O was added, the temperature was controlled at 60°C, and the reaction time was 2 h. 60 g of fluorine-containing compound and 550 mL of recycled mother liquor were obtained. Among them, the fluoride ion concentration in the recycled mother liquor was 1.53 g / L, and the ratio of the molar number of the defluorinating agent to the molar number of the theoretical addition amount was approximately 0.850:1.
[0123] Example 2
[0124] (1) Take 550 mL of the recycled mother liquor obtained in Example 1 and mix it with 450 mL of pure water, add sulfuric acid to prepare a H2SO4 solution with a concentration of 50 g / L, and preheat it to 60°C.
[0125] (2) Weigh 500 g of dried tantalum-niobium tailings sample (the same as in Example 1) into a beaker, add the H2SO4 solution prepared in step (1); maintain 60°C, stir at 600 r / min for 2 h, and filter to obtain 1175 mL of leaching solution and 198 g of washing residue.
[0126] (3) The concentration of total iron (TFe) in the leaching solution is 75 g / L, Fe 3+ The concentration is 21.5g / L, 15g of iron filings are added to the solution, stirred and reacted at 60℃ for 1h, and filtered while hot to obtain 1100mL of purified liquid and 7.5g of reduced iron slag.
[0127] (4) The purified liquid was boiled under stirring, concentrated until a small amount of crystals precipitated, cooled to 15°C and filtered to obtain 350 g of crude ferrous sulfate heptahydrate and 375 mL of crystallization mother liquor.
[0128] (5) Dissolve the crude ferrous sulfate heptahydrate in 60°C water, cool to 15°C with stirring, and recrystallize three times to obtain 295 g of ferrous sulfate with a purity greater than 98%.
[0129] (6) The mother liquor of the first recrystallization was mixed with the mother liquor of the crystallization to obtain 480 mL of mixed liquid, and the pH value was adjusted to 5.0 with sodium hydroxide. The fluoride ion concentration in the mixed liquid was detected to be 45 g / L; 125 g of defluorinating agent MgSO4·7H2O was added, the temperature was controlled at 60°C, and the reaction time was 2 h. 67 g of fluorine-containing compound and 540 mL of recycled mother liquor were obtained. Among them, the fluoride ion concentration in the recycled mother liquor was 1.82 g / L, and the ratio of the molar number of the defluorinating agent to the molar number of the theoretical addition amount was approximately 0.858:1.
[0130] Example 3
[0131] (1) Take 200 mL of the recycled mother liquor obtained in Example 2, add sulfuric acid to prepare a H2SO4 solution with a concentration of 20 g / L, and preheat to 60°C.
[0132] (2) Weigh 200 g of dried tantalum-niobium tailings sample (the same as in Example 1) into a beaker, add the H2SO4 solution prepared in step (1); maintain 60°C, stir at 600 r / min for 2 h, and filter to obtain 212 mL of leaching solution and 88 g of washing residue.
[0133] (3) The concentration of total iron (TFe) in the leaching solution is 94 g / L, Fe 3+ The concentration is 23.7 g / L, 6 g of iron filings are added to the solution, stirred at 60°C for 1 hour, and filtered while hot to obtain 206 mL of purified liquid and 4 g of reduced iron slag.
[0134] (4) The purified liquid was boiled under stirring, concentrated until a small amount of crystals precipitated, cooled to 20°C and filtered to obtain 92.5 g of crude ferrous sulfate heptahydrate and 105 mL of crystallization mother liquor.
[0135] (5) Dissolve the crude ferrous sulfate heptahydrate in 60°C water, cool to 20°C with stirring, and recrystallize three times to obtain 65.6 g of ferrous sulfate with a purity of 98.5%.
[0136] (6) The mother liquor from the first recrystallization was mixed with the mother liquor from the crystallization to obtain 150 mL of mixed liquid, and the pH value was adjusted to 6.0 with sodium hydroxide. The fluoride ion concentration in the mixed liquid was detected to be 52 g / L. 30 g of defluorinating agent Y2(SO4)3 was added, the temperature was controlled at 65°C, and the reaction time was 4 h. 47 g of fluorine-containing compound and 140 mL of recycled mother liquor were obtained. Among them, the fluoride ion concentration in the recycled mother liquor was 1.25 g / L, and the ratio of the molar number of the defluorinating agent to the molar number of the theoretical addition amount was approximately 0.940:1.
[0137] Example 4
[0138] (1) Weigh 500 g of the above-mentioned dried tantalum-niobium tailings sample into a beaker, add 1000 mL of H2SO4 solution preheated to 60°C and with a concentration of 50 g / L; maintain 60°C, stir at a speed of 600 r / min for 2 h, and filter to obtain 1175 mL of the first leachate and 195 g of the first washing slag.
[0139] The first leaching solution was mixed with 500 g of the above-mentioned tantalum-niobium tailings, stirred at 60° C. and 600 r / min for 2 h, and then filtered to obtain 1260 mL of the second leaching solution and 280 g of the second washing residue.
[0140] The second leaching solution was mixed with 500 g of the above-mentioned tantalum-niobium tailings, stirred at 60° C. and 600 r / min for 2 h, and then filtered to obtain 1350 mL of the third leaching solution and 480 g of the second washing residue.
[0141] (2) The concentration of total iron (TFe) in the third leaching solution was 155 g / L, Fe 3+ The concentration is 43.8 g / L, 25 g of iron filings are added to the solution, stirred and reacted at 60°C for 1 hour, and filtered while hot to obtain 1300 mL of purified liquid and 16.5 g of reduced iron slag.
[0142] (3) The purified liquid was directly cooled to 10°C without concentration to obtain 720 g of crude ferrous sulfate heptahydrate and crystallization mother liquor.
[0143] (4) Dissolve the crude ferrous sulfate heptahydrate in 60°C water, cool to 10°C with stirring, and recrystallize three times to obtain 550 g of 98.5% pure ferrous sulfate and recrystallization mother liquor.
[0144] (5) A total of 1600 ml of the mixture of crystallization mother liquor and recrystallization mother liquor was added to adjust the pH to 5.0, and the fluoride ion concentration was detected to be 89.4 g / L. 850 g of defluorination agent MgSO4·7H2O was added, the temperature was controlled at 60°C, and the reaction time was 2 h. 60 g of fluoride-containing slag and 1550 mL of recycled mother liquor were obtained. The fluoride ion concentration in the recycled mother liquor was 1.33 g / L.
[0145] Example 5
[0146] The method is basically the same as Example 4, except that the cooling temperature in step (3) is different; specifically, the final temperature of the purified liquid directly cooled in Example 5 is 25°C.
[0147] Comparative Example 1
[0148] The method is basically the same as Example 1, except that the leaching temperature in step (2) is different. Specifically, in Comparative Example 1, the tantalum-niobium tailings are mixed with dilute sulfuric acid, stirred at 25° C. and filtered. Other parameters are the same as in Example 1.
[0149] Comparative Example 2
[0150] The method is basically the same as Example 1, except that the recrystallization temperature in step (5) is different. Specifically, the crude ferrous sulfate heptahydrate in Comparative Example 2 is dissolved in 100° C. water. Other parameters are the same as those in Example 1.
[0151] The recovery rate of ferrous sulfate and the defluorination rate of the mother liquor in the above examples and comparative examples were calculated, and the results are shown in Table 2.
[0152] Iron recovery rate = total iron content in crystallized ferrous sulfate / (total iron content in tantalum-niobium tailings + iron powder content) × 100%
[0153] Mother liquor defluorination rate = (1-recycled mother liquor fluorine content / mother liquor fluorine content) × 100%
[0154] Table 2
[0155]
[0156] In Comparative Example 1, the leaching solution was washed and filtered at 25°C, but crystals precipitated when the iron concentration reached about 1.5 mol / L. The precipitated ferrous sulfate crystals made filtering difficult, resulting in reduced recycling efficiency and longer recycling time.
[0157] In Comparative Example 2, the high temperature used for concentration will cause the ferrous sulfate heptahydrate to transform, resulting in a decrease in solubility and a change of crystals from green to white precipitate.
[0158] Compared with Example 1, in Example 2, the recycled mother liquor after adjusting the pH and concentration of dilute sulfuric acid was used to leach the tantalum-niobium tailings, which significantly improved the iron recovery rate. The reason is that the recycled mother liquor still contains some iron ions, which can effectively improve the recovery rate of ferrous sulfate. Further, although the recycled mother liquor was also used in Example 3, the concentration of the dilute sulfuric acid solution in Example 3 was lower than that in Example 2, so the iron recovery rate of Example 3 was lower than that of Example 2.
[0159] Example 4 uses a cyclic re-immersion method to saturate the solution, which reduces the solution concentration step compared to Example 1 and has a higher yield.
[0160] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0161] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for treating tantalum-niobium tailings produced by a hydrofluoric acid-sulfuric acid process, characterized in that: The steps include: The tantalum-niobium tailings obtained by the hydrofluoric acid-sulfuric acid process are mixed with a dilute sulfuric acid solution, stirred and reacted at 40°C to 80°C for 30min to 300min, and filtered to obtain a leachate and a washing residue; The leaching solution is mixed with iron powder to undergo a reduction reaction, and filtered to obtain a purified solution; The purified liquid is subjected to cooling and crystallization treatment, and filtered to obtain crude ferrous sulfate and crystallization mother liquor; The pH value of the crystallization mother liquor is adjusted to 2.0-6.0 by using a pH adjusting agent, mixed with a defluorinating agent for defluorination reaction, and filtered to obtain a fluorine-containing compound and a recycled mother liquor.
2. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to claim 1, characterized in that: The processing method further comprises the following steps: Dissolving the crude ferrous sulfate at 60° C. to 70° C., and obtaining ferrous sulfate and a recrystallization mother liquor by recrystallization and filtration; The pH value of the recrystallization mother liquor is adjusted to 2.0-6.0 by using a pH adjusting agent, mixed with a defluorinating agent for defluorination reaction, and filtered to obtain a fluorine-containing compound and a recycled mother liquor.
3. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to claim 1, characterized in that: Before the leaching solution is mixed with the iron powder for reduction reaction, the following steps are also included: The leaching solution is mixed with tantalum-niobium tailings, stirred and reacted at 40° C. to 80° C. for 30 min to 300 min, and filtered while keeping warm.
4. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to claim 1, characterized in that: The concentration of the dilute sulfuric acid solution is 10 g / L to 50 g / L.
5. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to claim 1, characterized in that: The volume ratio of the dilute sulfuric acid solution to the mass ratio of the tantalum-niobium tailings is (0.5 mL to 2 mL): 1 g; Optionally, the mass ratio of the volume of the dilute sulfuric acid solution to the tantalum-niobium tailings is (2 mL~3 mL): 1 g.
6. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to any one of claims 1 to 5, characterized in that: The tantalum-niobium tailings obtained by the hydrofluoric acid-sulfuric acid process are mixed with the recycled mother liquor and dilute sulfuric acid solution.
7. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to any one of claims 1 to 5, characterized in that: The processing method meets at least one of the following characteristics: (1) In the step of obtaining the leaching solution and the washing residue by heat preservation filtration, the temperature of the heat preservation filtration is 55°C to 65°C; (2) The final temperature of the cooling crystallization is 10°C to 25°C; (3) The temperature of the defluorination reaction is 50°C to 70°C, and the time is 1h to 5h.
8. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to any one of claims 1 to 5, characterized in that: The ratio of the molar number of the iron powder to the molar number of the iron powder theoretically required for the reduction reaction is (1.2-2):
1.
9. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to any one of claims 1 to 5, characterized in that: The processing method meets at least one of the following characteristics: (1) The defluorination agent includes one or more of magnesium sulfate, aluminum sulfate, sodium sulfate and rare earth sulfate; (2) The pH adjuster includes one or more of ammonia water, ammonium bicarbonate, sodium hydroxide and sodium carbonate.
10. The method for treating tantalum-niobium tailings produced by the hydrofluoric acid-sulfuric acid process according to any one of claims 1 to 5, characterized in that: The ratio of the molar number of the defluorinating agent to the molar number of the defluorinating agent theoretically required for the defluorinating reaction is (0.85-1):1.
Citation Information
Cited By
Method for separating tantalum-niobium smelting slag
CN121674704A